Educating in the New Visual Processes: Abstraction and metaphor in the digital microscopy (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2020)
We expose the most relevant features of digital micrography for an artistic and educational reading; we begin by understanding these scientific-technical images, for further epistemological and aesthetic analysis. This visual corpus allows to show the image as a process and as a device of knowledge, and not just an appearance. The ability of micrography to translate and convert information into visual metaphors, gives it a growing interest for research and practice in Visual Arts.
Keywords: Array; visual metaphor; Iconicity; Augmented reality; Microscopy